2014
DOI: 10.1111/pce.12260
|View full text |Cite
|
Sign up to set email alerts
|

Elevated [CO2] does not ameliorate the negative effects of elevated temperature on drought‐induced mortality in Eucalyptus radiata seedlings

Abstract: It has been reported that elevated temperature accelerates the time-to-mortality in plants exposed to prolonged drought, while elevated [CO2] acts as a mitigating factor because it can reduce stomatal conductance and thereby reduce water loss. We examined the interactive effects of ) and two temperature (ambient and ambient +4°C) treatments. Seedlings were exposed to two controlled drying and rewatering cycles, and then water was withheld until plants died. The extent of xylem cavitation was assessed as loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 62 publications
(180 reference statements)
7
102
0
1
Order By: Relevance
“…Most previous studies on the impact of eCO 2 associated with drought and/or elevated temperature did not report whole ecosystem responses, but primarily plant responses at various organizational levels. Generally, they show that eCO 2 alleviates the stress associated with drought and/or elevated temperature (4,16,18,(22)(23)(24)(25)(26)(27)(28), but some studies found inconsistent responses (29)(30)(31)(32)(33)(34)(35)(36). This variability could be linked with the seasonality of precipitation (35,37) or with the intensity and length of the imposed stress, because the effect of eCO 2 has been shown to be positive under moderate drought and negligible under severe stress when stomata are fully closed (14).…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies on the impact of eCO 2 associated with drought and/or elevated temperature did not report whole ecosystem responses, but primarily plant responses at various organizational levels. Generally, they show that eCO 2 alleviates the stress associated with drought and/or elevated temperature (4,16,18,(22)(23)(24)(25)(26)(27)(28), but some studies found inconsistent responses (29)(30)(31)(32)(33)(34)(35)(36). This variability could be linked with the seasonality of precipitation (35,37) or with the intensity and length of the imposed stress, because the effect of eCO 2 has been shown to be positive under moderate drought and negligible under severe stress when stomata are fully closed (14).…”
Section: Resultsmentioning
confidence: 99%
“…Thus the effects of hotter drought in reducing photosynthesis and plant water availability may have much larger negative impacts on phloem transport than the benefits of lowered viscosity (e.g., Hö lttä et al 2009. Experimental data indicate trees can die faster under drought conditions that are warmer, as exhibited in 13 of 14 species from 11 different genera recently studied (Adams et al 2009, Duan et al 2014; see also earlier related research by Daubenmire 1943). Consequently, shorter drought events that previously were non-lethal can become lethal with climate warming, producing more frequent tree mortality events (Fig.…”
Section: Temperaturementioning
confidence: 98%
“…Strong climate warming consensus, increasing climate extremes expected, including increased frequency of rapid swings between opposite precipitation extremes IPCC 2012, 2014, Cai et al 2015 Forest ''browning'' observed in some regions in some years Jong et al 2012, Yi et al 2014 Hotter drought can cancel out CO 2 fertilization and increased water-use efficiency, as can insect herbivory Jentsch et al 2007, Warren et al 2011, Franks et al 2013, Duan et al 2014, Lévesque et al 2014, Couture et al 2015 MC 3…”
Section: Observationsmentioning
confidence: 99%
“…The deleterious effects of heatwaves on photosynthesis might be even more pronounced if they occur with greater frequency in cooler spring months when physiological mechanisms for coping with heat stress may be downregulated. Elevated CO 2 often does not lead to enhanced photosynthetic performance or survival of heatwave events (Bauweraerts et al 2014;Duan et al 2014). In some cases, photosynthetic and leaf area responses to growth temperature suggest intraspecific variation in the thermal response of some Eucalyptus species (Drake et al 2015).…”
Section: Introductionmentioning
confidence: 99%